2012
DOI: 10.1021/ef300862u
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thermophysical and Transport Properties for the CFD Simulations of In-Cylinder Biodiesel Spray Combustion

Abstract: This paper reports the development, validation, and application of the thermophysical and transport properties of coconut, palm, and soy methyl esters for fuel spray and combustion modeling under light-duty diesel engine conditions. The developed fuel library is implemented in an open-source CFD code. The fuel properties are validated for both constant volume combustion chamber and compression ignition (CI) engine operation at a wide range of conditions. Sensitivity analysis on the effects of individual fuel p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 25 publications
0
60
0
1
Order By: Relevance
“…The evaporation rate of SME shown in Figure 6 is slightly higher than that of PME at the beginning 3 CAD for all levels of engine power, which is then followed by slight fluctuations at similar magnitudes between the two fuels. At low temperatures, SME has similar vapour pressure as compared to PME, but lower surface tension leading to a higher initial evaporation rate [20]. SME and PME demonstrate different combustion characteristics at different engine powers although their IDs are similar.…”
Section: Biodieselmentioning
confidence: 97%
See 2 more Smart Citations
“…The evaporation rate of SME shown in Figure 6 is slightly higher than that of PME at the beginning 3 CAD for all levels of engine power, which is then followed by slight fluctuations at similar magnitudes between the two fuels. At low temperatures, SME has similar vapour pressure as compared to PME, but lower surface tension leading to a higher initial evaporation rate [20]. SME and PME demonstrate different combustion characteristics at different engine powers although their IDs are similar.…”
Section: Biodieselmentioning
confidence: 97%
“…The initial evaporation rates are of concern here as they directly affect the IDs. It is observed that within 4 CAD from the SOI, diesel fuel demonstrates the highest evaporation rate which can be attributed to its physical properties of diesel [20]. The surface tension, vapour pressure and density of diesel are at values favourable to high evaporation rate.…”
Section: Dieselmentioning
confidence: 97%
See 1 more Smart Citation
“…However, as the SoI timing approached closer to TDC, the effect of fuel properties on mixing processes significantly reduced. Ismail et al [229] performed fuel spray and combustion modeling of coconut methyl ester (CME), palm methyl ester (PME), and Soyabean methyl ester (SME) using the measured fuel properties. Since each methyl ester is from a different source, the composition of each ester was analyzed and the properties were measured for an individual biodiesel.…”
Section: Physical Properties Of Biodiesel and Spray Modelingmentioning
confidence: 99%
“…Hexadecanoic acid, methyl ester 17 Octadecanoic acid, methyl ester 9 9-Octadecenoic acid, methyl ester 30 9, 12-Octadecadienoic acid, methyl ester 44 Fig. 23 Experimental and numerical axial penetration length for (a) PME vapor and liquid and (b) PME, CME, SME, and mineral diesel in liquid phase [229] Fig. 25, the updated constants could capture biodiesel spray characteristics based on reference results.…”
Section: Physical Properties Of Biodiesel and Spray Modelingmentioning
confidence: 99%